Electrokinetic and electrostatic properties of bilayers containing gangliosides GM1, GD1a, or GT1. Comparison with a nonlinear theory. - McDaniel, R V (1986)
We formed vesicles from mixtures of egg phosphatidylcholine (PC) and the gangliosides GM1, GD1a, or GT1 to model the electrokinetic properties of biological membranes. The electrophoretic mobilities of the vesicles are similar in NaCl, CsCl, and TMACl solutions, suggesting that monovalent cations do not bind significantly to these gangliosides. If we assume the sialic acid groups on the gangliosides are located some distance from the surface of the vesicle and the sugar moieties exert hydrodynamic drag, we can describe the mobility data in 1, 10, and 100 mM monovalent salt solutions with a combination of the Navier-Stokes and nonlinear Poisson-Boltzmann equations. The values we assume for the thickness of the ganglioside head group and the location of the charge affect the theoretical predictions markedly, but the Stokes radius of each sugar and the location of the hydrodynamic shear plane do not. We obtain a reasonable fit to the mobility data by assuming that all ganglioside head groups project 2.5 nm from the bilayer and all fixed charges are in a plane 1 nm from the bilayer surface. We tested the latter assumption by estimating the surface potentials of PC/ganglioside bilayers using four techniques: we made 31P nuclear magnetic resonance, fluorescence, electron spin resonance, and conductance measurements. The results are qualitatively consistent with our assumption.